Association between socio demographic, work factors, fatigue and emotion regulation with commuting riding behaviors among workers in Selangor, Malaysia - Jaafa, Noor Hidayah (2023)
The rising trend of commuting accidents has caused worrisome conditions whereas more than 30 000 cases were reported and 76.9% were motorcyclists and pillion riders. Despite numerous research have been conducted to explore the causes of these issues yet there was still a lack of information regarding the relationship between work factors, fatigue, emotion regulation, and commuting behaviour. Thus, this study aims to determine the relationship between work factors, fatigue, and emotion regulation with commuting riding behaviour in Selangor. This cross-sectional study involved 430 workers (male: 5.5%; females: 13.6%) with average age was 34 were randomly selected in Selangor. Convenient sampling was done, followed by purposive sampling of respondents based on the inclusive and exclusive criteria. Self-administered questionnaire consisting standardized questionnaire were used to collect information on sociodemographic and work factors, occupational fatigue exhaustion / recovery scale (OFER), cognitive emotion regulation questionnaire (CERQ) and commuting riding behaviour (SMRBQ) among respondents. The most prevalent unsafe riding behaviour reported was related toward time and money opportunistic (1.85 ± 0.59). In multiple linear regressions, being male (β = 0.23, p<.01) and young (β = 0.2, p<.01) who had experienced in a road crash (β = 0.1, p<.05) which also possessed self-blame (β = 0.09, p<.01), putting into perspective (β = 0.08, p<.01) and chronic fatigue (β = 0.04, p<.05) would predict 20% variance in riding behaviour among workers in Selangor. Therefore, it can be concluded gender and age factor, emotion regulation condition and level of fatigue should be considered in improving the CRB of workers in Selangor.